2019
DOI: 10.1111/ajad.12964
|View full text |Cite
|
Sign up to set email alerts
|

Case Series: Limited Opioid Withdrawal With Use of Transdermal Buprenorphine to Bridge to Sublingual Buprenorphine in Hospitalized Patients

Abstract: Background-Prerequisite opioid withdrawal symptoms prior to buprenorphine induction are unacceptable to many patients. We assessed whether transdermal buprenorphine minimized withdrawal while bridging to sublingual therapy among hospital inpatients.Methods-Retrospective chart review of (n = 23) inpatients with opioid use disorder or opioid dependence due to chronic pain.Results-Of 23 inpatients, 65% transitioned without symptoms, while 35% experienced mild withdrawal. Ninety-six percent completed planned hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 18 publications
0
59
0
1
Order By: Relevance
“…27,[35][36][37][38][39][40][48][49][50]52,54,55 Transdermal buprenorphine was used exclusively in 2 protocols. 46,51 Two protocols provided multiple buprenorphine formulations. 47,53 Buprenorphine sublingual or buccal dosing varied widely, from a first-day total dose of 600 μg 27 to a maximum possible dose of 32 mg. 49,50 Nine protocols divided administration into 2 to 4 doses per day.…”
Section: Rotation Protocolsmentioning
confidence: 99%
See 3 more Smart Citations
“…27,[35][36][37][38][39][40][48][49][50]52,54,55 Transdermal buprenorphine was used exclusively in 2 protocols. 46,51 Two protocols provided multiple buprenorphine formulations. 47,53 Buprenorphine sublingual or buccal dosing varied widely, from a first-day total dose of 600 μg 27 to a maximum possible dose of 32 mg. 49,50 Nine protocols divided administration into 2 to 4 doses per day.…”
Section: Rotation Protocolsmentioning
confidence: 99%
“…Rotation to buprenorphine was associated with decreased pain severity in 12 of 17 studies (70.6%). 35,36,42,43,[46][47][48][49][50][51][52]54 For example, Roux et al 36 found that higher doses of buprenorphine were associated with better pain control among participants. Under the highest dose condition (16 mg vs 2 mg), the McGill Pain Questionnaire scores significantly decreased (odds ratio, 0.42; 95% CI, 0.20-0.90).…”
Section: Pain Severity and Interferencementioning
confidence: 99%
See 2 more Smart Citations
“…Unlike traditional induction, buprenorphine micro-dosing allows for initiation of buprenorphine without requiring a period of opioid withdrawal. Successful protocols utilizing sublingual (SL) 7 , 8 , 9 , 10 and transdermal 11 forms have been reported. Micro-dosing is intended to both improve tolerability and decrease duration of induction.…”
Section: Introductionmentioning
confidence: 99%